Pharmacokinetics, Distribution in Serum Lipoproteins and Tissues, and Renal Toxicities of Amphotericin B and Amphotericin B Lipid Complex in a Hypercholesterolemic Rabbit Model: Single-Dose Studies - Wasan, Kishor M. (American Society for Microbiology, 1998)
The purpose of this study was to determine if a relationship exists among total serum and lipoprotein cholesterol concentration, the severity of amphotericin B (AmpB)-induced renal toxicity, and the serum pharmacokinetics of AmpB in hypercholesterolemic rabbits administered AmpB and AmpB lipid complex (ABLC). After 10 days of cholesterol-enriched diet (0.50% [wt/vol]) or regular rabbit diet (control), each rabbit was administered a single intravenous bolus of AmpB or ABLC (1.0 mg/kg of body weight). Blood samples were obtained before administration and serially thereafter for the assessment of serum pharmacokinetics, kidney toxicity, and serum lipoprotein distribution. Rabbits were humanely sacrificed after all blood samples were obtained, and tissues were harvested for drug analysis. Before drug treatment, cholesterol-fed rabbits demonstrated marked increases in total serum cholesterol and low-density lipoprotein (LDL) cholesterol levels compared with levels in rabbits on a regular diet. No significant differences in triglyceride levels were observed. A significant increase in serum creatinine levels was observed in cholesterol-fed and regular diet-fed rabbits administered AmpB. However, the magnitude of this increase was 2.5-fold greater in cholesterol-fed rabbits than in regular diet-fed rabbits. No significant differences in triglyceride levels were observed. A significant increase in serum creatinine levels was observed in cholesterol-fed and regular diet-fed rabbits administered ABLC. Whereas AmpB pharmacokinetics were significantly altered in cholesterol-fed rabbits administered free AmpB, similar AmpB pharmacokinetics were observed in both rabbit groups administered ABLC. Renal AmpB levels were significantly increased in cholesterol-fed rabbits administered AmpB compared with those in all other groups. Hepatic and lung AmpB levels were elevated in cholesterol-fed rabbits administered free AmpB compared to controls. In addition, hepatic, lung, and spleen AmpB levels were significantly decreased in cholesterol-fed rabbits administered ABLC compared to controls. An increased percentage of AmpB was recovered in LDL–very-low-density lipoprotein fraction when free AmpB was administered to cholesterol-fed rabbits compared with those in all other groups. These findings suggest that increases in cholesterol, specifically, LDL cholesterol levels, modify the disposition and renal toxicity of free AmpB. However, the pharmacokinetics and renal toxicity of ABLC were independent of elevations in total and LDL cholesterol levels.